2015
DOI: 10.1182/blood-2014-03-562660
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is required for stem cell mobilization by G-CSF

Abstract: Key Points• G-CSF activates autophagy in HSCs and neutrophils.• The response and survival of HSCs mobilized by G-CSF in vivo require autophagy.Granulocyte colony-stimulating factor (G-CSF) is widely used clinically to prevent neutropenia after cytotoxic chemotherapy and to mobilize hematopoietic stem cells (HSCs) for transplantation. Autophagy, a process of cytoplasmic component recycling, maintains cellular homeostasis and protects the cell during periods of metabolic stress or nutrient deprivation. We have o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Contrary to mice, in which all leukocyte subpopulations exhibited signs of enhanced autophagic flux, only neutrophils from healthy volunteers presented an increased number of LC3B C puncta, in line with previous findings showing autophagy activation in this population. 54,55 In addition, it has been previously demonstrated that detection of autophagy in neutrophils can be used to monitor autophagic flux at the whole body level in the context of pathological settings. 56 At present, the reasons for this discrepancy between mice and humans with respect to autophagy induction in all leukocyte subpopulation and neutrophils only, respectively, are elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to mice, in which all leukocyte subpopulations exhibited signs of enhanced autophagic flux, only neutrophils from healthy volunteers presented an increased number of LC3B C puncta, in line with previous findings showing autophagy activation in this population. 54,55 In addition, it has been previously demonstrated that detection of autophagy in neutrophils can be used to monitor autophagic flux at the whole body level in the context of pathological settings. 56 At present, the reasons for this discrepancy between mice and humans with respect to autophagy induction in all leukocyte subpopulation and neutrophils only, respectively, are elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of My-D88, an adaptor protein required for most TLR signaling, attenuated the G-CSFinduced effect on HSCs [4]. More recently, Mouttie et al reported that G-CSF could enhance autophagy in HSCs [77]. Autophagy was previously suggested to be required for HSC maintenance [78].…”
Section: Extracellular Signals Regulating Hscsmentioning
confidence: 99%
“…However, the use of such agents to potentiate the effects of chemotherapy may be efficacious in some settings. Additionally, modulation of autophagy is likely to have several deleterious effects such as diminishing G-CSF response 6 , impairment of normal HSC function 2 and altering T-cell homeostasis 5 .…”
mentioning
confidence: 99%
“…Within the hematopoietic system, autophagy has diverse roles and is required for hematopoietic stem cell (HSC) function 2 , differentiation into erythroid 3 or T-lymphoid lineages 4,5 and response to extracellular cytokine signaling 6 . In blood cancers such as acute myeloid leukaemia (AML), modulating autophagy has been proposed as a novel therapy to treat AML 1,7,8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation